2021
DOI: 10.1097/shk.0000000000001814
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Regional Optimization: Increasing the Therapeutic Window for Endovascular Aortic Occlusion In Traumatic Hemorrhage

Abstract: Resuscitative endovascular balloon occlusion of the aorta (REBOA) allows for effective temporization of exsanguination from non-compressible hemorrhage (NCTH) below the diaphragm. However, the therapeutic window for aortic occlusion is time-limited given the ischemia-reperfusion injury generated. Significant effort has been put into translational research to develop new strategies to alleviate the ischemia-reperfusion injury and extend the application of endoaortic occlusion. Targeted regional optimization (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…This result is concordant with the single-center study, 28 which concluded that partial REBOA may be associated with less end-organ dysfunction than complete REBOA. The results are also concordant with a large (and growing) body of preclinical literature documenting reduced ischemia/reperfusion injury in animals treated with partial compared with complete endovascular aortic occlusion 24,27,32,33 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result is concordant with the single-center study, 28 which concluded that partial REBOA may be associated with less end-organ dysfunction than complete REBOA. The results are also concordant with a large (and growing) body of preclinical literature documenting reduced ischemia/reperfusion injury in animals treated with partial compared with complete endovascular aortic occlusion 24,27,32,33 …”
Section: Discussionsupporting
confidence: 84%
“…The results are also concordant with a large (and growing) body of preclinical literature documenting reduced ischemia/reperfusion injury in animals treated with partial compared with complete endovascular aortic occlusion. 24,27,32,33 While the data on pREBOA-PRO represent current clinical use, the limited market release at select level I trauma centers may limit the generalizability of the findings. Furthermore, there are known limitations of registry studies, including missing data and lack of a nontreated control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, these guidelines are based on complete aortic occlusion. pREBOA allows for partial occlusion and thus a variable degree of distal blood flow [7][8][9]. A flow rate of 0.5 L/min has been shown to be effective at preventing ischemia while minimizing hemorrhage in swine [10].…”
Section: Discussionmentioning
confidence: 99%
“…Distal ischemia and Ischemia-Reperfusion-Injury (IRI) is often blamed for the hemodynamic instability associated with aortic occlusion (19). Interestingly, the more classical serologic indicators of IRI, such as lactate or creatinine kinase, were not significantly different among cohorts (Table 1).…”
Section: Discussionmentioning
confidence: 99%